From slave abuse to hate crime : the criminalization of racial violence in American history - Aaronson, Ely (Cambridge historical studies in American law and society, 2014)
"This book explores the complex ways in which political debates and legal reforms regarding the criminalization of racial violence have shaped the development of American racial history. Spanning previous campaigns for criminalizing slave abuse, lynching, and Klan violence and contemporary debates about the legal response to hate crimes, this book reveals both continuity and change in terms of the political forces underpinning the enactment of new laws regarding racial violence in different periods and of the social and institutional problems that hinder the effective enforcement of these laws. A thought-provoking analysis of how criminal law reflects and constructs social norms, this book offers a new historical and theoretical perspective for analyzing the limits of current attempts to use criminal legislation as a weapon against racism"--